Crop productivity, nutritional and economic benefits of no-till systems in smallholder farms of Ethiopia - Mupangwa, Walter; Yahaya, Rabe; Tadesse, Ephrem; Ncube, Bongani; Mutenje, Munyaradzi; Chipindu, Lovemore; Mhlanga, Blessing; Kassa, Abrham (MDPI, 2023)
Smallholder maize and wheat production systems are characterized by high drudgery. On-farm trials were run for three seasons in Ethiopia. The study assessed the effect of 2 WT direct seeding and growing season on (1) soil quality, and (2) maize and wheat productivity, energy and protein gains, and gross margins, on smallholder farms in Ethiopia. For the wheat crop, the effect of different soil types and agroecological conditions on productivity was assessed. The treatments in paired plots were (i) conventional ploughing practice and (ii) no-till (NT). Soil properties, crop yield, nutrition gains and gross margins were determined. No-till improved soil properties in the short term. No-till produced 1210–1559 kg ha􀀀1 grain, 18–29 GJ ha􀀀1 energy and 121–194 kg ha􀀀1 proteins, and generated 358–385 US$ ha􀀀1 more than the conventional practice in the maize system. In the wheat system, no-till treatment had 341–1107 kg ha􀀀1 grain, 5–16 GJ ha􀀀1 energy and 43–137 kg ha􀀀1 proteins, and generated 230–453 US$ ha􀀀1 more than conventional practice. No-till can be more productive and profitable in the Ethiopian maize and wheat-based cropping systems.